Avaliação biomecânica in vitro de três técnicas de fixação interna rígida utilizadas em osteotomia sagital do ramo mandibular: estudo em mandíbulas de carneiro - Oliveira, Leandro Benetti de (2010)
Among the osteotomies performed in orthognathic surgery, the sagittal ramus mandibular osteotomy (SRMO) is the most common , allowing a great width of movements and rigid internal fixation (RIF), therefore eliminating the need of maxillomandibular block in the postoperative period. The purpose of this work was to evaluate the biomechanical resistance of three systems used for RIF.The study was performed in 30 sheep hemi mandibles divided into 3 groups with 10 hemi mandibles The samples were measured to avoid discrepancies among them and submitted to SRMO with a 5mm advancement, afterwards. In group I, 2.0 x 12 mm screws were used for fixation, inserted positionally in an inverted "L" configuration (inverted "L" group). In group II, fixation was performed with two 2.0 x 12 mm screws, inserted positionally in a linear configuration and a straight mini plate with four holes and four 2.0 x 6.0 mm monocortical screws (hybrid group). In group III, fixation was performed with two straight miniplates of four holes and eight 2.0 x 6.0 mm monocortical screws (I mini plate group). All material used for RIF was from Sin - Osteosin® company. The hemimandibles were submitted to linear load vertical test by a unit of Kratos K2000MP mechanical tests for loading registration and displacement. The results showed that there were no differences statistically significant between the tested groups.